RESPON GURU DALAM MENYIKAPI PERUBAHAN KURIKULUM (Studi Kasus Pada Madrasah Aliyah Negeri 1 Kudus) - Efferi, Adri (Pascasarjana IAIN Kudus, 2017)
The curriculum is important in the world of education. Teachers play an important role in the change of a curriculum. Therefore, the determining factor for the successful implementation of the curriculum is the understanding of teachers, the core of the curriculum. This study aims to assess the level of teachers' understanding of the curriculum in 2013 and their responses to those changes. This study used a qualitative approach with interviews as the main data collection techniques. After collecting and analyzing the data, the results are as follows: with respect to the level of understanding of the teachers of the curriculum, would still need to be always serious attention especially by the leadership of the madrasas, such as teachers' understanding of the principles of learning, creation of lesson plans and assessment in accordance curriculum 2013. Regarding the response of teachers to address the changes to the curriculum, that is two some accept and some are refused. Although teachers actually realize that a change or innovation implies the change of a condition long to become better.